Evaluation of the Force Required to Move a Coalesced Liquid Droplet along a Fiber - Mead-Hunter, Ryan; Mullins, Benjamin; Becker, Thomas; Braddock, R. (American Chemical Society, 2010)
This work presents a theoretical model describing the force required to move a coalesced liquid droplet along an oleophilic filter fiber. Measurements have been made using the atomic force microscope (AFM) to examine these forces over a range of fiber and droplet diameters as well as oil properties. Good agreement between measured and modeled forces was found. The influence of droplet displacement perpendicular to the fiber on the force required to move the droplet has also been determined experimentally and theoretically. It was found that fiber surface inhomogeneities are likely to influence results. This work has also established empirical relationships that can be used to predict the force, based on a known droplet volume, for the liquid types used.